If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -1x + 8y = -16 Solving -1x + 8y = -16 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-8y' to each side of the equation. -1x + 8y + -8y = -16 + -8y Combine like terms: 8y + -8y = 0 -1x + 0 = -16 + -8y -1x = -16 + -8y Divide each side by '-1'. x = 16 + 8y Simplifying x = 16 + 8y
| 3-y^2+y^2=5 | | f(-x)=x^2+5x+3 | | 60+0.3x=x | | 5x-8=(6m+4) | | -7/2w=5/6 | | -7/2w5/6 | | 5+y*y=36 | | -2=9/8v | | 3.00=0.45b | | x+15=3x-7 | | 13x+3-4x=3x-8 | | 1/4a=4 | | 7h-6=4h+3 | | 5p+9=3p+13 | | (3x-4)(5x+15)=0 | | -96-58=-1894 | | 3m=7(m+6) | | 11=(-2x+2)+5 | | 38x+16=54 | | 36+3x=12x | | 9w=56+w | | 2x-3x+18=-4x-4 | | 4n+65=93 | | U=48n+210+7n+7 | | 18+2x=6y | | 1x+30=2x | | Y=2/9x-7 | | 1x+54=7x | | 2=10/3z=3z-7/3 | | 1/16a^2-1/25=0 | | a=8+b | | U=6*8n+6*35+7*n+7*1 |